A new golden yellow small-flowered Cyrtochilum species (Orchidaceae: Oncidiinae) from Peru - Dalström, Stig (Universidad de Costa Rica, 2020)
A new golden yellow small-flowered species of Cyrtochilum is described and illustrated with a line drawing and photographs. It is compared with superficially similar species in the C. aureum complex, in which the new species differs by the lack of lacerate column wings typical for that group. It is distinguished from all other known small-flowered Cyrtochilum species by the golden yellow color in combination with the distinctly pandurate lip lamina where the front lobe is wider than the basal lobes combined.